Accelerating Educational Administrative Services through School Principal Supervision in Secondary Education - Tajul Fazari; Sahdan Sahdan (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2026)
The transformation of educational administrative services has become a crucial aspect in developing a responsive, efficient, and professional education system in the digital era. This study aims to describe the role of the school principal in accelerating educational administrative services through Sergiovanni’s Five Forces supervision model at SMA Negeri 15 Takengon. A descriptive qualitative approach was employed, using data collection techniques such as in-depth interviews, participatory observations, and documentation. The findings indicate that the principal implements all five supervisory forces in a synergistic manner: technical force through the use of digital applications and standardized operating procedures; human force through empathetic and participatory communication; educational force through staff training and competency development; symbolic force through exemplary leadership and the embodiment of ethical values; and cultural force through the reinforcement of a collaborative and values-based work culture. The implementation of these five forces not only enhances the efficiency of administrative services but also fosters a reflective, loyal, and character-driven organizational culture. The main contribution of this study lies in offering a contextual and applicable principal supervision model to accelerate the quality of administrative services in secondary schools, particularly in regions with limited resources.